Photocatalytic Removal of the Greenhouse Gas Nitrous Oxide by Liposomal Microreactors. (5th September 2022) - Piper, Samuel E. H.; Casadevall, Carla; Reisner, Erwin; Clarke, Thomas A.; Jeuken, Lars J. C.; Gates, Andrew J.; Butt, Julea N.
Abstract: Nitrous oxide (N2 O) is a potent greenhouse and ozone‐reactive gas for which emissions are growing rapidly due to increasingly intensive agriculture. Synthetic catalysts for N2 O decomposition typically contain precious metals and/or operate at elevated temperatures driving a desire for more sustainable alternatives. Here we demonstrate self‐assembly of liposomal microreactors enabling catalytic reduction of N2 O to the climate neutral product N2 . Photoexcitation of graphitic N‐doped carbon dots delivers electrons to encapsulated N2 O Reductase enzymes via a lipid‐soluble biomolecular wire provided by the MtrCAB protein complex. Within the microreactor, electron transfer from MtrCAB to N2 O Reductase is facilitated by the general redox mediator methyl viologen. The liposomal microreactors use only earth‐abundant elements to catalyze N2 O removal in ambient, aqueous conditions. Abstract : Self‐assembled liposome microreactors mimic the spatial separation of redox reactions seen in respiration and photosynthesis. Catalytic reduction of the climate heating gas N2 O to benign N2 by encapsulated enzyme is driven by irradiation of external carbon dots through an electron transfer pathway defined by a membrane‐spanning cytochrome and redox‐cycling of internal methyl viologen.